The Effects Of Presentation Method And Learning Skill Toward English Abilities For Eleventh Grade Students At Senior High Schools In East Lampung - Sukoco, Pudjiono (Jurnal Pedagogy, 2017)
Learning activities is an educational process which has various ways and can give the impacts of student’s learning English abilities. In fact most students find some difficulties specially in mastering English lesson at school. The different views about learning in educational process are met in the kind of initial conclusion that education is a process of preparing the young generation learning to live out and fulfill their destiny more effectively and efficiently. Some of the ways to make students are able to master an English lesson is by presentation method and students learning skill. The research has the following objectives: to determine the effects of presentation method on student abilities; to determine the influences of students’ learning skill to students’ abilities; to determine the effects of presentation method and student skill to students English abilities. The result obtained that the value of tcount is greater than ttable by calculating the Fvalue of 7.976. Medium Ftable (0,05) N = 30 is equal with 2.92. So Fcount > Ftable or 7.976 > 2.92. Therefore, H0 is rejected and Ha is accepted. It can be concluded that the method of presentation and student learning skill together give positive impacts toward student English ability. From the summary table is obtained the value of Rsquare of 0.371. This means that the two independent variables X1 and X2 together can influent of 37.1% and the balance of 62.9% affected by other factors that are not observed by the researcher.